(untitled) (University Heart Journal, 2011)
Carotid Endarterectomy (CEA) performed in combination with coronary artery bypass grafting (CABG) have also increased steadily since Bernhard and colleague’s initial report in 1972. Coexistence of symptomatic coronary artery disease and significant carotid artery stenosis ranges from 3.4% to 22%. The incidence of postoperative stroke after CABG ranges from 0.7% to 5%. Coronary revascularization in a patient with internal carotid artery stenosis more than 50% is associated with a postoperative stroke rate of 6%, which increases significantly to more than 16% when stenosis is more than 90%. To reduce the potential risk for postoperative stroke after CABG in patients with significant or symptomatic carotid artery stenosis, many surgeons have advocated combined CABG with unilateral carotid endarterectomy. However, clinical experience with the concomitant approach is conflicting. On the basis of the long-term results, it is estimated that simultaneous carotid endarterectomy and myocardial revascularization in conjunction with cardiopulmonary bypass is a method safe enough to prefer its routine use with acceptable low operative risk and satisfactory long-term morbidity. The overall 30-day mortality of combined CABG with bilateral carotid endarterectomy was 6.1% and that was unrelated to primary cardiac or cerebrovascular events. Favorable outcome also supports the justification for performing concomitant coronary artery bypass grafting with bilateral carotid endarterectomies in selected patients. Key words: Carotid endarterectomy; Coronary Bypass Grafting. DOI: 10.3329/uhj.v6i1.7194 University Heart Journal Vol.6(1) 2010 pp.41-44